2021
DOI: 10.1080/19336918.2021.1935407
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of exosome-derived microRNAs reveals insights of intercellular communication during invasion of breast, prostate and glioblastoma cancer cells

Abstract: Mazzanti (2021) Analysis of exosomederived microRNAs reveals insights of intercellular communication during invasion of breast, prostate and glioblastoma cancer cells,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
(87 reference statements)
2
3
0
Order By: Relevance
“…Our NanoString data showed that there were at least 25 highly expressed miRNAs in all three GSC lines and that 8 of the 25 miRNAs (mir320e, mir520f-3p, mir363-3p, mir144-4p, mir16-5p, mir495-3p, mir23a-3p, mir155-5p) have a seed sequence to target PTEN, whilst 3 of the 25 miRNAs (mir612, mir142-3p, mir551a) were found to be common in the Glioblastoma Bio Discovery Portal of the TCGA database. This is in line with previous publications showing that miRNAs packaged within EVs can modulate the intercellular communications within the brain microenvironment [ 15 , 50 , 51 , 52 ], as well as playing a role in how the tumour responds to therapy [ 53 ]. There were many abundantly expressed miRNAs found in the EVs of T98G cells subjected to invasion [ 51 ] and serum EVs [ 52 ] involved in glioma progression [ 54 ], yet only a few miRNAs were found in common with our study, expressing at low levels ( Supplementary Table S2 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our NanoString data showed that there were at least 25 highly expressed miRNAs in all three GSC lines and that 8 of the 25 miRNAs (mir320e, mir520f-3p, mir363-3p, mir144-4p, mir16-5p, mir495-3p, mir23a-3p, mir155-5p) have a seed sequence to target PTEN, whilst 3 of the 25 miRNAs (mir612, mir142-3p, mir551a) were found to be common in the Glioblastoma Bio Discovery Portal of the TCGA database. This is in line with previous publications showing that miRNAs packaged within EVs can modulate the intercellular communications within the brain microenvironment [ 15 , 50 , 51 , 52 ], as well as playing a role in how the tumour responds to therapy [ 53 ]. There were many abundantly expressed miRNAs found in the EVs of T98G cells subjected to invasion [ 51 ] and serum EVs [ 52 ] involved in glioma progression [ 54 ], yet only a few miRNAs were found in common with our study, expressing at low levels ( Supplementary Table S2 ).…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous publications showing that miRNAs packaged within EVs can modulate the intercellular communications within the brain microenvironment [ 15 , 50 , 51 , 52 ], as well as playing a role in how the tumour responds to therapy [ 53 ]. There were many abundantly expressed miRNAs found in the EVs of T98G cells subjected to invasion [ 51 ] and serum EVs [ 52 ] involved in glioma progression [ 54 ], yet only a few miRNAs were found in common with our study, expressing at low levels ( Supplementary Table S2 ). This is probably due to the type and heterogeneity of the cell lines studied; nevertheless, it indicates that EVs do specifically package certain miRNAs to modulate the tumour microenvironment and the intercellular communication between tumour cells and the surroundings.…”
Section: Discussionsupporting
confidence: 92%
“…The MicroRNAs (miRNAs) regulate gene expressions in tumor and tumor-adjacent tissue [72]. Lorusso et al explained that miRNAs could facilitate communication between tumor cells and their surroundings and control tumor immunity by directly regulating genes associated with immune stimulation or inactivation [73].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are present in almost all body fluids, including plasma/serum, saliva, breast milk, cerebrospinal fluid, urine and semen (131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141). Exosomes are also distributed in the TME and carry cargo including a variety of proteins, DNA, mRNA, miRNA, long noncoding RNA, and even virus/prion genetic material (142)(143)(144)(145)(146). Exosomes play a key role in local and remote intercellular communication in cancer and are an important part of the TME.…”
Section: Exosomesmentioning
confidence: 99%